Autism spectrum disorder screening in children aged 16-30 months using the Modified Checklist for Autism in Toddlers-Revised (M-CHAT-R) - Clarissa Josephine Aditya; Jenni Kim Dahliana; Ariani Dewi Widodo; Rini Sekartini (Indonesian Pediatric Society, 2021)
Background Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder with a global prevalence of 7.6 in 1,000 children. The Modified Checklist for Autism in Toddlers - Revised (M-CHAT-R) is one of many screening tools for ASD. It is fast, easy to use, and has been translated and validated in the Indonesian language. Objective To determine the prevalence of ASD in Indonesia and its risk factors. Methods A cross-sectional study was conducted from March to October 2020. In the first protocol (March to July 2020), 219 children aged 16-30 months from 20 hospital walk-in clinics in five districts of Jakarta were included. Subjects’ parents filled out the M-CHAT-R questionnaire during their visit. A series of questions were asked to provide information about probable risk factors associated with ASD: gender, family history of ASD, preterm birth, low birth weight (LBW), and history of seizures. The second protocol (August to October 2020) was completed by parents via an online form, where 746 children aged 16-30 months were enrolled. Therefore, a total of 965 subjects were eligible for statistical analysis. Results Of 965 subjects, 56.58% were males. Subjects’ mean of age was 22.59 (SD 4.15) months. M-CHAT-R screening showed that 34 (3.52%) subjects were at high risk of developing ASD. Only male gender was significantly associated with ASD. Conclusion We screened for ASD in healthy 16-30-month-old Indonesian children. The rate of high-risk M-CHAT-R score was 3.52%. Male gender was a significant risk factor for high-risk M-CHAT-R results.